1997
DOI: 10.1063/1.475173
|View full text |Cite
|
Sign up to set email alerts
|

On the à and B̃ electronic states of NCO and its clusters with nonpolar solvents

Abstract: The B←X and Ã←X transitions of the NCO radical and its clusters with nonpolar solvents are studied in a supersonic jet expansion by employing laser-induced fluorescence techniques. Fluorescence excitation ͑FE͒ and hole burning spectra are recorded for the NCO radical and compared to previous work. NCO is clustered with Ar, N 2 , CH 4 , and CF 4 nonpolar molecules to elucidate the effect of solvation on the radical energy levels and dynamics. FE spectra are detected for NCO 1:1 clusters showing blue shifts in t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
20
0

Year Published

1999
1999
2017
2017

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 12 publications
(20 citation statements)
references
References 48 publications
0
20
0
Order By: Relevance
“…13,14 Subsequently, there have been several investigations using absorption, 15,16 stimulated emission pumping, [17][18][19] and laser-induced fluorescence ͑LIF͒. [20][21][22][23][24][25][26][27] Additionally, the spectroscopy of the B 2 ⌸ state was examined in the photodissociation experiments by Cyr et al 6 Several of these studies have also provided insight into the dynamical processes that NCO undergoes upon dissociation. Figure 1 illustrates the energy level diagram for NCO and its lowest energy fragmentation channels.…”
Section: Introductionmentioning
confidence: 99%
“…13,14 Subsequently, there have been several investigations using absorption, 15,16 stimulated emission pumping, [17][18][19] and laser-induced fluorescence ͑LIF͒. [20][21][22][23][24][25][26][27] Additionally, the spectroscopy of the B 2 ⌸ state was examined in the photodissociation experiments by Cyr et al 6 Several of these studies have also provided insight into the dynamical processes that NCO undergoes upon dissociation. Figure 1 illustrates the energy level diagram for NCO and its lowest energy fragmentation channels.…”
Section: Introductionmentioning
confidence: 99%
“…[14][15][16] In the fluorescence excitation experiments, a general valve pulsed nozzle is used to generate an adiabatic expansion of the appropriate mixture of molecular precursor for Xcpd ͑Ͻ1% of the total pressure͒, the solvent gas ͑0.1%-10% of the total pressure͒, and 50-400 psi He expansion gas. The stainless steel vacuum chamber into which the mixture is expanded remains at ϳ10 Ϫ4 Torr during the FE experiment.…”
Section: A Experimentalmentioning
confidence: 99%
“…Nonetheless, relatively few studies involving radicals and clusters can be found in the literature, due in part to the significantly increased difficulties encountered in generating, isolating, cooling, and clustering these short lived, reactive species. Of particular note for cluster studies of radicals are those involving OH-Ne, N 2 , H 2 , 9 NH, CH-rare gases, 10 CN-Ne, 11 C 2 H 3 O-Ar, 12 C 5 H 5 -He, Ne, N 2 , 13 C 5 H 4 CH 3 -He, Ne, 13 and CH 3 O, 14 NCO, 15 and C 6 H 5 CH 2 /Ar, N 2 , CH 4 , C 2 H 6 , and C 3 H 8 . 16 Reports involving vdW clusters of aromatic radicals are limited to the benzyl, cyclopentadienyl, and methylcyclopentadienyl radicals to the best of our knowledge.…”
Section: Introductionmentioning
confidence: 99%
“…To model the excited state behavior of Xcpd-nonpolar solvent clusters we employ the Xcpd-Ar cluster data to fit C, H, X parameters under a number of simplifying assumptions. 8,9,12 These parameters are in turn employed to understand the other cluster spectra; in general, this program is reasonably successful.…”
Section: Introductionmentioning
confidence: 99%